Pentingnya Ilmu Parenting Terhadap Pertumbuhan dan Perkembangan Anak Usia Dini Di Pedesaan - Risqiyah, Zahrotur; Adawiyah , Robiatul (Jurnal Ilmu Keperawatan Anak, 2024)
Early childhood is a critical period of growth and development influenced by genetic factors, environment and parental patterns. During this period, children's physical, mental, social and emotional development is very rapid, so that the quality of parenting has a major influence on children's lives. Parents play an important role in good parenting through proper parental knowledge. Parenting is not only about fulfilling basic needs such as eating and sleeping, but also psychological, moral and social aspects that support children's overall growth and development. In rural areas, access to parental information is limited due to lack of infrastructure and technology, thus affecting parents' ability to provide optimal care. This study was conducted with the aim of determining the importance of parental education for the growth and development of young children in rural areas and to identify the obstacles faced by parents in utilizing education. from parents. The results of this study are expected to provide recommendations for improving the quality of education and supporting parents in villages.